Polyphosphoesters : chemistry and application - Troev, Kolio D. (Kolio Dimov), 1944- (Elsevier insights., 2012)
Polyphosphoesters are a multifunctional, environmentally friendly, and cost-efficient material, making them an important subject. The design of this type of material plays a key role in the progress of industry, agriculture, and medicine. This book introduces the chemistry, characterization and application of polyphosphoesters including comprehensive coverage of poly(alkylene H-phosphonate)s, poly(alkylene phosphate)s, poly(alkyl or aryl phosphonate)s, and poly(alkyl phosphite)s and poly(alkyl phosphinite)s. Each polymer is discussed in detail including methods, properties, and applications. This book is useful for students and practitioners preparing to work, or in the process of working, in the exciting field of polymer chemistry. Presents a unique look at an important, multifunctional and environmentally friendly material. Outlines methods used to prepare different polyphosphoesters Comprehensive examination of the properties of polyphosphoesters.